Cardiac CT angiography in the emergency room: Apical hypertrophic cardiomyopathy presenting as acute coronary syndrome. Issue 5 (7th March 2017) - Turner, Michael C.; Kerut, Edmund K.; Mckinnie, James; Davis, Michael; Hinton, Christine
Abstract : A 59‐year‐old male presented to the emergency room with symptoms of chest tightness and palpitations. Following conversion of atrial fibrillation to sinus rhythm, he had deep symmetrical T‐wave changes on his electrocardiogram. Symptoms resolved almost immediately, and his initial troponin was negative. He underwent cardiac CT angiography utilizing an emergency room triage protocol which resulted in a diagnosis of nonobstructive coronary artery disease and apical hypertrophic cardiomyopathy. Following a hospital stay of less than 24 hours, he was discharged to outpatient follow‐up on medical management and has remained asymptomatic over 6 months. This case presentation illustrates an example of the diversity of pathology that presents in emergency rooms with symptoms consistent with acute coronary syndrome.